Perancangan set furniture ergonomis aktivitas kerja kantor - Kamdhani, Kathleen Eugene; Kusumarini, Yusita; Suprobo, Filipus Priyo (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
Desk and sitting facilities are important factors in creating a physical work environment that affects the performance and effectiveness of work activities in office. The important factors that influence this design are ergonomics and the correct working posture. Most office activities in Indonesia, are performed in static position for a long period of time, which is bad for health in the future. In this study, there are 3 problems that are raised. First, how to solve static work position problem, and Does body posture affect fatigue and user comfort and whether facility dimensions, behaviour, and time period factors are related to stress intensity. This study uses design thinking as a method with 3 stages: inspiration (understand, observe, and point of view), ideation (ideate, prototype, and test), and implementation (storytelling, pilot, business model canvas). This design resulted in 3 sets of alternative designs and 1 set of real sit-stand work facilities, such as standing chair and standing desk. The product set tested by respondents to find the evaluation of ergonomic factors, time division for dynamic work positions, and recommendations for dynamic work designs with ergonomic principles for development and improvement of the product in the future